1981
DOI: 10.1002/eji.1830111002
|View full text |Cite
|
Sign up to set email alerts
|

Role of β1H for the binding of C3b‐coated particles to human lymphoid and phagocytic cells

Abstract: Coating of EAC14oxy23b with highly purified human serum beta 1H globulin (beta 1H) led to acceleration of rosette formation with human peripheral blood lymphocytes (PBL), tonsil lymphocytes, B lymphoblastoid (Raji) cells, granulocytes and monocytes. This reaction was discernible from C3bi-dependent rosette formation. Enhancement of rosette formation of C3b cells by beta 1H was most effective at limiting amounts of C3 per EAC14oxy23b. The beta 1H effect was not due to trace contamination with C3b inactivator. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
(3 reference statements)
1
14
0
Order By: Relevance
“…Little is known about receptors for factor H, although there is evidence for their presence on the surfaces of B lymphocytes [25][26][27], monocytes [28][29][30], and neutrophils [31]. Lambris and Ross [32] and Erdei and Sim [33] isolated factor H binding proteins from the surface of lymphoblastoid cells; other studies of putative factor H cell surface receptors have relied on functional or binding data [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about receptors for factor H, although there is evidence for their presence on the surfaces of B lymphocytes [25][26][27], monocytes [28][29][30], and neutrophils [31]. Lambris and Ross [32] and Erdei and Sim [33] isolated factor H binding proteins from the surface of lymphoblastoid cells; other studies of putative factor H cell surface receptors have relied on functional or binding data [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that monocytes and PMN have receptors for C3b and C3bi (6,7,29 (33). Additionally, Ehlenberger and Nussenzweig suggested that C3d on the surface of a particle coated with suboptimal amounts of IgG augmented monocyte phagocytosis of that particle (32 (1983) 2355 rosetting with cultured monocytes than is required for EAC3d rosette formation with Raji cells (unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…C3b-coated erythrocytes were prepared as described (Schmitt et al, 1981). Briefly, sheep erythrocytes (E) were sensitized with subagglutinating rabbit anti-sheep erythrocyte serum (Amboceptor, Behring).…”
Section: Lys Pro Ser Leu Gly Ser Gly Alamentioning
confidence: 99%